Hydrocarbon contaminated water remediation using a locally constructed multi-stage bioreactor incorporated with media filtration - S. Antwi-Akomea; B. Fei-Baffoe; E.J.D. Belford; M. Borigu (Global Journal of Environmental Science and Management)
The present study investigated the coupling effect of biodegradation and media filtration in treating hydrocarbon contaminated water. The study recorded reductions in total petroleum hydrocarbon, total dissolved solids, turbidity and microbial load. The study was essentially a simulated pump and treat process that involved the pumping of hydrocarbon contaminated water for treatment in a locally designed multi-stage bioreactor incorporated with media filtration. A mixed consortium of hydrocarbon-eating microbes was applied in the study. Hydrocarbon-eating microbes were isolated from hydrocarbon contaminated soils obtained from selected mechanic workshops. Bamboo chips and coconut husk chips were applied as support media for microbial attachment within the bioreactor compartment of the treatment setup. Applied support media were approximately 2-4 cm in size. Media filters applied comprised three locally manufactured candle filters two of which were respectively impregnated with granular activated charcoal and sand. The coupling effect of biodegradation and media filtration recorded over 99 % (> 8.7 mg/L) total petroleum hydrocarbon removal. Microbial load reduction ranged from 3.57±0.11E+20 to 7.45±0.26E+20 Colony forming unit/mL, total dissolved solids reduction from 30.00±5.66 to 131.00±0.00 mg/L and turbidity reduction from 39.00±1.41 to 123.50±0.71 nephelometric turbidity units. Biodegradation accounted for 69.70±0.63 and 90.72±2.36 % total petroleum hydrocarbon removal respectively for bamboo chips and coconut husk chips.